Implementasi Program Pemberdayaan Ekonomi Masyarakat Pesisir di Kecamatan Belang Kabupaten Minahasa Tenggara - SAMPUL, YULVIANI IRENE; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this research is to know the implementation process of economic empowerment program ofcoastal community in Belang Subdistrict of South Minahasa Regency. This is due to poorly targeted aid,poor quality of beneficiary community resources, misuse of relief goods, and lack of cooperation betweenthe Office of Marine and Fisheries with the District Government. To be able to describe the implementationof economic empowerment program of coastal community in District Belang Regency of South Minahasa,researcher use descriptive qualitative research method. Data obtained through primary and secondary datasources with interviewing, obserfasi and document review techniques. Data analysis is done by datacollection, data reduction, data presentation, and conclusion. The results of this study indicate that thisprogram is quite helpful in improving the economy of the community but in its implementation is still foundthat the distribution of aid that is not on target and with limited human resources of the beneficiaryfishermen groups resulted in the misuse of relief goods. Recommendations that can be put forward are bytightening the data collection of fishermen groups, providing maximum assistance to each group andmaking a statement not to abuse the relief items received.Keywords: Policy Implementation, Economic Empowerment, Coastal Communities.